Relationship between muscle strength, balance and gait speed among knee osteoarthritis patients with sarcopenia and non-sarcopenia / Farahin Kamarudin and Chua Siew Kuan - Kamarudin, Farahin; Chua, Siew Kuan (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Sarcopenia and Osteoarthritis (OA) are degenerative musculoskeletal condition affects physical functioning in adults. This study aimed to compare the muscle strength, balance and gait speed (GS) between knee OA patients with sarcopenic and non-sarcopenic, and investigate the relationship of muscle strength, balance and GS among knee OA patients with sarcopenic and non-sarcopenic. A cross-sectional study recruited 57 knee OA participants aged 45-74 years (54 females, 3 males) from primary health care clinic. SARC-F questionnaire was used to screen sarcopenia status. Knee extensor strength (KES) and hand grip strength (HGS) were assessed by hand-held dynamometer. Balance and GS measured by tandem stand and four-meter walk test, respectively. The Mann-Whitney U test was used to compare the muscle strength and physical performances between knee OA patients with sarcopenic and non-sarcopenic. Spearman's correlation was used to evaluate the association between muscle strength and physical performance and anthropometric variables. There were significant (p < 0.05) lower of HGS, GS and balance in knee OA with sarcopenic group compared to non-sarcopenic group. Both balance (rs= 0.40, p <0.05) and left calf circumference (rs= 0.42, p < 0.05) was correlated with HGS in knee OA patients with sarcopenic group. Gait speed (rs= 0.36, p < 0.05) and right and left calf circumference (rs= 0.54-0.55, respectively, both p < 0.05) were correlated with HGS in knee OA patients. Muscle strength is age-associated and may affect balance among sarcopenic knee OA group. Thus, include muscle strength training and improve balance may prevent sarcopenia in patients with knee OA group.